PENGELOLAAN SAMPAH BERBASIS BUMKAL - misbawati, yenni (Jurnal Riset Daerah, 2022)
The non-optimal performance of waste management is an important problem for Bantul Regency. The volume of Bantul waste that enters the Piyungan landfill continues to increase. One of the comprehensive efforts and steps to achieve the waste management performance target in Bantul Regency and minimize the amount of waste sent to the Piyungan TPA is to carry out complete waste management in each village. This study aims to map the potential of Badan Usaha Milik Kalurahan (BUMKal) in managing waste at the Kalurahan level. The research method used is a qualitative method with a descriptive approach. The data analysis technique used refers to the interactive analysis model from Miles. Data obtained in the form of primary data by conducting discussions with selected informants by purposive sampling, observation and literature study. The research was conducted by understanding the conditions of waste management in the village, identifying and understanding the existing problems, then mapping the potential for developing BUMKal-based waste management. The results showed that in general, in order for BUMKal's waste management in the Kalurahan to run optimally, it was necessary to adjust the building design, add equipment and infrastructure and provide an increase in management capacity and human resources.